2022
DOI: 10.1152/ajpheart.00476.2021
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of murine myocardial infarct size using 2-D and 4-D high-frequency ultrasound

Abstract: Background: Ischemic heart disease is the leading cause of death in the United States, Canada, and worldwide. Severe disease is characterized by coronary artery occlusion, loss of blood flow to the myocardium, and necrosis of tissue, with subsequent remodeling of the heart wall, including fibrotic scarring. The current study aims to demonstrate the efficacy of quantitating infarct size via 2D echocardiographic akinetic length and 4D echocardiographic infarct volume and surface area as in vivo analysis techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…We conducted the strain analysis using a 4D Strain Toolbox. This custom software enables the visualization and quantification of 4DUS data to produce a 3D strain map over an entire cardiac cycle 48,49 . We first oriented the 4D images and centered them to PLAX, SAX, and coronal views of the left ventricle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted the strain analysis using a 4D Strain Toolbox. This custom software enables the visualization and quantification of 4DUS data to produce a 3D strain map over an entire cardiac cycle 48,49 . We first oriented the 4D images and centered them to PLAX, SAX, and coronal views of the left ventricle.…”
Section: Methodsmentioning
confidence: 99%
“…We manually adjusted the contours over the cardiac cycle using four SAX planes and three PLAX planes. Next, the software created a 4D mesh of the contours from which measurements of global cardiac function (e.g., ejection fraction, stroke volume) and regional function (strain, volume) can be extracted 48,49 . Custom toolbox cardiac wall motion with border tracings can be visualized in Video S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ischemia, there is altered LV shortening and elevated S strain, with no apparent change in RV strain. Dann et al 7 compared murine strain magnitudes after LV ischemia and reported significant reductions in LV free-wall shortening within the first seven days post ligation. Clinically, myocardial strain imaging is gaining traction as an indicator of heart function.…”
Section: Simulated Ischemiamentioning
confidence: 99%
“…Over the past few years, we have developed methods for high-sensitivity spatiotemporal mapping of 4D (3D + time) gated cardiac echocardiographic data [23][24][25][26]. These advances have allowed us to identify subtle imaging biomarkers in a variety of cardiac disease animal models of myocardial infarction [27,28], aortic aneurysm [29,30], and atherosclerosis [31]. Applying these techniques to 3D + time cardiovascular magnetic resonance (CMR) images offers a promising method for biomechanical characterization of pathologic changes in DMD patients.…”
Section: Introductionmentioning
confidence: 99%